Safety of everolimus with reduced calcineurin inhibitor exposure in de novo kidney transplants: an analysis from the randomized TRANSFORM study - Tedesco-Silva, Helio; Pascual, Julio; Viklicky, Ondrej; Basic-Jukic, Nikolina; Cassuto, Elisabeth; Kim, Dean Y.; Cruzado, Josep M.; Sommerer, Claudia; Adel Bakr, Mohamed; Garcia, Valter D.; Uyen, Huynh-Do; Russ, Graeme; et al. (Transplantation, 2019)
Background. The safety profiles of standard therapy versus everolimus with reduced-exposure calcineurin inhibitor (CNI) therapy using contemporary protocols in de novo kidney transplant recipients have not been compared in detail. Methods. TRANSFORM was a randomized, international trial in which de novo kidney transplant patients were randomized to everolimus with reduced-exposure CNI (N = 1014) or mycophenolic acid (MPA) with standard-exposure CNI (N = 1012), both with induction and corticosteroids. Results. Within the safety population (everolimus 1014, MPA 1012), adverse events with a suspected relation to study drug occurred in 62.9% versus 59.2% of patients given everolimus or MPA, respectively (P = 0.085). Hyperlipidemia, interstitial lung disease, peripheral edema, proteinuria, stomatitis/mouth ulceration, thrombocytopenia, and wound healing complications were more frequent with everolimus, whereas diarrhea, nausea, vomiting, leukopenia, tremor, and insomnia were more frequent in the MPA group. The incidence of viral infections (17.2% versus 29.2%; P < 0.001), cytomegalovirus (CMV) infections (8.1% versus 20.1%; P < 0.001), CMV syndrome (13.6% versus 23.0%, P = 0.044), and BK virus (BKV) infections (4.3% versus 8.0%, P < 0.001) were less frequent with everolimus. CMV infection was less common with everolimus versus MPA after adjusting for prophylaxis therapy in the D+/R− subgroup (P < 0.001). Study drug was discontinued more frequently due to rejection or impaired healing with everolimus, and more often due to BKV infection or BKV nephropathy with MPA. - Conclusions. De novo everolimus with reduced-exposure CNI yielded a comparable incidence, though a distinctly different pattern, of adverse events versus current standard of care. Both regimens are safe and effective, yet their distinct profiles may enable tailoring for individual kidney transplant recipients.